y=3-4x соответственно 3x-3+4x=11
x=4 из этого следует 16+y=3
ответ: y=-13;x=4
(х;у)=(2;-5).
Пошаговое объяснение:
{4х+у=3, у=3-4х.
{3х-у=11. 3х-(3-4х)=11
3х-3+4х=11
7х-3=11
7х=11+3
7х=14
х=14÷7
х = 2
у=3-4*2
у=3-8
у = - 5
ответ : ( 2 ; - 5 ).
ответ : ( х; y ) = ( 2; -5 )
Проверка :
Верно - ✔︎
y=3-4x соответственно 3x-3+4x=11
x=4 из этого следует 16+y=3
ответ: y=-13;x=4
(х;у)=(2;-5).
Пошаговое объяснение:
{4х+у=3, у=3-4х.
{3х-у=11. 3х-(3-4х)=11
3х-3+4х=11
7х-3=11
7х=11+3
7х=14
х=14÷7
х = 2
у=3-4*2
у=3-8
у = - 5
ответ : ( 2 ; - 5 ).
ответ : ( х; y ) = ( 2; -5 )
Проверка :
Верно - ✔︎